Computerized stabilometry in assessing the results of puncture vertebroplasty in patients with vertebral osteoporosis - I. E. Poverennova; D. R. Ikromova; Yu. S. Komarova; E. V. Khivintseva; S. A. Anan'eva (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Osteoporosis is often referred to as a "silent epidemic" because the decrease in bone mass is often asymptomatic until a fracture occurs. One of the most severe manifestations of the disease is osteoporosis of vertebral bodies, the fracture of which leads to disability. In spinal osteoporosis, the main cause of pathologic compression fractures is a fall due to impaired balance. The dynamics of balance dysfunction after surgical treatment of vertebral body compression fractures remains insufficiently studied. We performed a stabilometric study in 103 patients with osteoporosis of the spine complicated by compression fracture at the thoracic and lumbar levels in the age range from 44 to 79 years. All patients underwent puncture vertebroplasty. It was demonstrated that patients with osteoporosis of the spine still have pronounced changes in the stabilogram parameters despite their positive dynamics. The most significant changes were noted in the energy expenditure index, 60% power spectrum level in the sagittal plane and dispersion of the deviation of the center of pressure in the horizontal plane. The persisting pronounced changes in stabilometric indices in the distant postoperative period make it necessary to perform rehabilitation to restore balance and gait.